One flew over the duck pond: Autoethnography, academic identity, and language. Issue 5 (November 2019) - Tienari, Janne
Autoethnography is about studying a community through the author's personal experience. I offer my autoethnography of moving from a Finnish-speaking business school to a Swedish-speaking one in Helsinki, Finland. This is my story as a Finnish speaker who works in English, develops a sense of lack and guilt for not contributing in Swedish, and enacts an identity of an outsider in his community. My ambivalent identity work as a privileged yet increasingly anxious white male professor elucidates connections between identity, language, and power, and it may enable me to see glimpses of what those who are truly marginalized and excluded experience. I argue that academic identity is based on language, and once that foundation is shaken, it can trigger self-reflection that helps to show how language is inevitably tied in with complex power relations in organizations. I offer my story as an invitation to discuss how we learn to deal with the complexity of identity work and language. My story lays bare how autoethnographies by the privileged, too, can be useful if they show the vulnerability we all experience in contemporary universities.